Redescription of Bactronophorus thoracites Gould (1856) and Bankia gracilis Moll (1935) from Sabah Waters, Malaysia, with Short Ecological Notes and Measurements Metrics - Loo Zhen Ann; Chen Cheng Ann; Khairul Adha Abd Rahim; Farah Diba (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchRedescription of marine woodborers, Bactronophorus thoracites and Bankia gracilis from the region were illustrated.New records of Bactronophorus thoracites and Bankia gracilis from the region.Addition info on the measurements of pallets was recorded.Certain ecological data on the habitat of marine woodborers Bactronophorus thoracites and Bankia gracilis were documented.AbstractMollusc wood-borers are classified into two groups: pholads and teredinids. While pholads have a limited distribution to temperate and tropical marine waters, teredinids are found worldwide. However, limited info on the taxonomy was documented on the marine wood borer in Sabah, Malaysia. Present study focuses on determining the wood borer species from Sabah waters, Malaysia. Samples were collected from fallen tree debris in the mangrove at Kota Kinabalu, Kuala Penyu and W.P. Labuan during low tide and water quality parameters were taken in-situ from all three sampling sites. Specimen identification was carried out by observing the physical characteristics of the pallets which are unique between genuses. The species Bactronophorus thoracites was identified from the Kota Kinabalu sampling site and species Bankia gracilis were found in both the Kuala Penyu and W.P. Labuan sampling site. The pallet of B. thoracite are of